2015
DOI: 10.1097/nna.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Linking Unit Collaboration and Nursing Leadership to Nurse Outcomes and Quality of Care

Abstract: Creating a care environment of strong collaboration among care providers and nursing leadership can help hospitals maintain a competitive nursing workforce supporting high quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 23 publications
1
72
0
3
Order By: Relevance
“…Such attributes of the work environment include interdisciplinary collaboration and administrative support to professional nursing practice, two recommendations explicitly stated in the IOM report ''Future of Nursing: Leading Change, Advancing Health'' as strategies to improve quality of care (IOM, 2011). In a recent study by Ma and colleagues, nursephysician relations and administrative support to nursing practice were found significantly associated with surgical readmissions among Medicare patients (Ma et al, 2015b). In another study, the researchers found that better teamwork between nurses and physicians/nurses and stronger nursing leadership at the unit-level were associated with better nurse outcomes and quality of care (Ma et al, 2015b).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Such attributes of the work environment include interdisciplinary collaboration and administrative support to professional nursing practice, two recommendations explicitly stated in the IOM report ''Future of Nursing: Leading Change, Advancing Health'' as strategies to improve quality of care (IOM, 2011). In a recent study by Ma and colleagues, nursephysician relations and administrative support to nursing practice were found significantly associated with surgical readmissions among Medicare patients (Ma et al, 2015b). In another study, the researchers found that better teamwork between nurses and physicians/nurses and stronger nursing leadership at the unit-level were associated with better nurse outcomes and quality of care (Ma et al, 2015b).…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study by Ma and colleagues, nursephysician relations and administrative support to nursing practice were found significantly associated with surgical readmissions among Medicare patients (Ma et al, 2015b). In another study, the researchers found that better teamwork between nurses and physicians/nurses and stronger nursing leadership at the unit-level were associated with better nurse outcomes and quality of care (Ma et al, 2015b). Moreover, there are resources that hospital administrators and unit managers can refer to for improving work environments, such as the TeamSTEPPS program (AHRQ, accessed on Janurary 29, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were reported by Ma et al. who examined the effects of unit collaboration (both nurse–nurse and nurse–physician) and nursing leadership on nurse outcomes and the quality of care. The study showed that improved collaboration was associated with decreased intent to leave the profession, improved quality of care reported by nurses and nurse job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Genel olarak hemşirelik hizmetleri yönetiminde kullanılan liderlik stilleri arasında otokratik, demokratik-katı-lımcı ve tam-serbesti tanıyan liderlik stillerinin yanı sıra görev odaklı liderlik yaklaşımlarından biri olan etkileşimci liderlik stili de yer almaktadır. 3,6,7,[20][21][22][23] Ayşe AKBIYIK ve ark.…”
Section: Hemşi̇reli̇k Hi̇zmetleri̇ Yöneti̇mi̇nde Li̇derli̇k Ve Kullanilan Li̇dunclassified
“…tarafından bahsedilen ve liderlik stili ile hasta sonuçları arasındaki ilişkiyi tanımla-yan bu teorinin geçerliliğini inceleyen çalışmalar mevcuttur. 3,7,[20][21][22][23] Yaşlı bakım evi, evde bakım hizmetleri ve hastaneler gibi çeşitli sağlık kurumlarında kesitsel, deneysel ve yarı deneysel araştırmalarda dönüşümcü liderlik stilinin hasta bakım kalitesini ve hasta güvenliğini dolaylı yoldan artırarak, hasta sonuçlarına pozitif yönden katkı sağladığı saptanmıştır. 2,21,[26][27][28][29][30][31] İlişki odaklı liderlik yaklaşımları ile yönetilen kliniklerde sağlık hizmeti ile ilişkili enfeksiyonlarda ve hasta mortalite oranlarında belirgin düzeyde azalma, hasta memnuniyetinde artış olduğu belirlenmiştir.…”
Section: Hemşi̇reli̇k Hi̇zmetleri̇ Yöneti̇mi̇nde Kullanilan Li̇derli̇k Sti̇lleunclassified